Temporal and spatial spread of potyvirus infection and its relationship to aphid populations visiting garlic crops - Perotto, Maria Cecilia (2014)
The potyviruses Onion yellow dwarf virus (OYDV) and Leek yellow stripe virus (LYSV) are the main causes of serious losses in garlic crops worldwide. Both viruses are transmitted by aphid vectors in a non-persistent manner. The relationships of aphid populations with temporal and spatial patterns of OYDV and LYSV were studied in a commercial main garlic production area from Mendoza, Argentina. The virus incidence in garlic plots during 2 years was quantified by a nitrocellulose-enzyme-linked immunosorbent assay. For temporal analyses performed in 2007 and 2008, disease progress curves were fitted using a logistic model. Epidemics were driven by non-colonising aphid species that spread the viruses primarily from west to east, coinciding with the wind pattern. This directional trend was reflected in the spatial analysis as a left-to-right gradient of virus incidence and cumulative aphid counts. Between 46 and 60 % of plants were infected with OYDV and LYSV in the first crop cycle exposed to natural infection. A checklist of aphid species visiting the garlic crop was generated, with 34 species detected. We found that total aphid catch is a better predictor of virus spread than catches of any single species or a combination of a few key species.